Hubungan Antara Level Emergency Severity Index (ESI) dengan Kepuasan Pasien di Instalasi Gawat Darurat Rumah Sakit Sido Waras - Regina Kurniasari (Universitas Airlangga, 2016)
The number of patients in Sido Waras Hospital Emergency Department declined since in 2013 until 2015 and the preliminary survey also showed there were complex complaints emergency department services. Therefore, the purpose of this study was to analyze the relationship between the service and the satisfaction of patients in Sido Waras Hospital Emergency Department.The concept of ESI Sido Waras Hospital Emergency Department namely provided categories of patients based on the gravity and duration of patient management.Therefore in this study to analyze the relationship with the ESI level of patient satisfaction in the Sido Waras Hospital Emergency Department. This study was a survey.Keywords : Emergency department, ESI level, patient satisfaction, service quality